Maximal operators of Schrödinger type with a complex parameter - Sjölin, Per (Mathematica Scandinavica, 2009)
Maximal operators of Schrödinger type but with a complex parameter are considered. For these operators we obtain results which in a certain sense lie between the results for the corresponding maximal operators for solutions to the Schrödinger equation and for solutions to the heat equation.